MENURUNKAN KECEMASAN IBU PRE PERSALINAN NORMAL DENGAN TERAPI SOUND HEALING - Chyntia Haryana; Asdi Lastari; Nayodi Permayasa (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2026)
Background: Normal childbirth often causes anxiety that can have a negative impact on the mother's physical and psychological condition. Purpose: One non-pharmacological effort that is starting to be used to reduce anxiety is sound healing therapy which utilizes soothing sound frequencies to create relaxation. Methods: This study is a Pre-Experimental study with the one group pretest posttest design. The study was conducted at the Independent Practice of Midwife Rusni Dewi in Padangsidimpuan City. The study population was 30 people, and all of them were used as samples (total sampling). Results: Data analysis was carried out univariately and bivariately using paired sample t-test at a 95% confidence level (α = 0.05). The results showed that most mothers before normal delivery at the Independent Practice of Midwife Rusni Dewi in Padangsidimpuan City experienced a decrease in anxiety from the severe category (70.0%; mean 30.13 ± 6.056) before therapy to the mild category (43.3%; mean 18.63 ± 4.860) after being given sound healing therapy. Statistical testing results showed that sound healing therapy was effective with an intervention duration of 20–40 minutes (a standard 30-minute session), administered twice weekly for four weeks (8 sessions) from 36 weeks of gestation until delivery, reducing maternal anxiety before normal labor. Conclusion: Midwives are recommended to utilize sound healing therapy as a supportive non-pharmacological method to provide emotional comfort to mothers approaching labor, and further research with larger sample sizes is encouraged to strengthen the scientific evidence.